UMP awarded with SEDA accreditation for energy efficiency - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) bagged the One Diamond Award for Low Carbon Buildings Assessment from Sustainable Energy Development Authority (SEDA) on December 13, 2019. UMP became the first university in the country to receive such an award for efforts taken that had successfully proved its ability to efficiently manage energy consumption, the use of renewable energy and reduce carbon dioxide gas emission. Green practice initiatives among Malaysians are highly encouraged especially when implementing ‘energy efficiency’ to reduce energy consumption. ‘Energy efficiency’ is the ultimate goal in effective and optimal energy consumption management, thus reducing wastage.